Relationship of COVID-19 pathogenesis for periodontal medicine research. Part II: Periodontal Medicine (Research, Society and Development, 2021)
The dysfunctional immunoinflammatory response to SARS-CoV-2 infection leads to excessive infiltration of monocytes, macrophages and T cells, non-neutralizing antibody, systemic cytokine storm, microthrombi mediated by tissue factor and oxidative stress, lower platelet counts, increased D-dimer, C-reactive protein and coagulation abnormalities, increased vascular permeability, pulmonary edema and pneumonia, and widespread inflammation and multi-organ damage. Periodontal diseases have a chronic and multifactorial inflammatory profile, of infectious origin, with bidirectional systemic interactions linked to over 50 systemic conditions/diseases. Immunoinflammatory response of periodontal tissues to the microbial challenge, protective/repair response and the local destruction of periodontium influence and are influenced by systemic conditions/diseases. Renin-angiotensin system/ACE inhibitors are also related to pathogenesis of COVID-19 by SARS-CoV-2-ACE2 and to pathogenesis of periodontitis, through bone resorption regulated by the ACE2/Ang-(1-7)/MasR axis and IL1-b, positive regulation of the kinin/receptor pathway B2 due to Toll-like receptor 2 inflammation and Th1/Th17 responses, the expression of the type 1 angiotensin II receptor in the inflamed gingival tissue, and modulating IL-1β-induced IL-6 production in human gingival fibroblasts. It is possible that SARS-CoV-2 infection increases local inflammatory events in periodontal tissue leading to destruction of periodontal tissues, probably enhanced by the systemic effects of periodontitis. Despite limited or non-existent scientific evidence on the effects of COVID-19 on periodontal diseases and their systemic interactions to date, it is possible to expect its impact on periodontal medicine research from the natural history of periodontal diseases to their pathogenesis and relationship with systemic conditions and response to treatment, as an environmental and acquired risk factor.